Classification of Multiple Sclerosis Clinical Profiles via Graph Convolutional Neural Networks - Marzullo, Aldo; Kocevar, Gabriel; Stamile, Claudio; Durand-Dubief, Françoise; Terracina, Giorgio; Calimeri, Francesco; Sappey-Marinier, Dominique (Frontiers in Neuroscience, 2019)
Recent advances in image acquisition and processing techniques, along with the success of novel deep learning architectures, have given the opportunity to develop innovative algorithms capable to provide a better characterization of neurological related diseases. In this work, we introduce a neural network based approach to classify Multiple Sclerosis (MS) patients into four clinical profiles. Starting from their structural connectivity information, obtained by diffusion tensor imaging and represented as a graph, we evaluate the classification performances using unweighted and weighted connectivity matrices. Furthermore, we investigate the role of graph- based features for a better characterization and classification of the pathology. 90 MS patients (12 clinically isolated syndrome, 30 relapsing-remitting, 28 secondary-progressive, and 20 primary- progressive) along with 24 healthy controls, were considered in this study. This work shows the great performances achieved by neural networks methods in the classification of the clinical profiles. Furthermore, it shows local graph metrics do not improve the classification results suggesting that the latent features created by the neural network in its layers have a much important informative content. Finally, we observe that graph weights representation of brain connections preserve important information to discriminate between clinical forms.